Daya Tetas Telur Hasil Persilangan Ayam Bangkok dan Ayam Ras Petelur (Isa brown) Menggunakan Ekstrak Daun Sirih Sebagai Bahan Sanitasi - Wa Ode Aprili sapta Nadira; Muh Rusdin; Astriana Napirah; Hamdan Has (Jurnal Ilmiah Peternakan Halu Oleo, 2023)
Abstrak. Using betel leaf extract as a sanitizer, this study aims to examine the hatchability of eggs resulting from crosses between Bangkok chickens and laying hens. This study used a randomized design with four treatments and five replications. There are five eggs in each repetition. The treatments tried were soaking eggs in 70% ethanol (P0), 5% betel leaf extract (P1), 10% betel leaf extract (P2), and 15% betel leaf extract separately (P3). in this study were organisms that had not yet developed practicality, mortality and hatchability. Analysis of variance using to tabulate and analyzed the data obtained. The Least Significant Difference Test using to continue the evaluation if the treatment has a significant effect on the variables studied. The mean embryo survival rates were 88% (P0), 91% (P1), 84% (P2), and 58% (P3), according to the findings. In each treatment, the average mortality rate was 12% (P0), 9% (P1), 16% (P2), and 42% (P3). hatchability was 56% (P0), 79.% (P1), 63% (P2), and 42% (P3). The use of betel leaf extract with different concentrations as egg cleaner from crosses between Bangkok and laying hens had a significant impact on embryo survival and mortality, but not on hatchability. The use of 5% betel leaf extract as a cleansing agent for hatching eggs showed that the embryos lived longer and died less frequently.